Enteromorpha prolifera polysaccharide prevents high‐ fat diet‐induced obesity in hamsters: A NMR‐based metabolomic evaluation. Issue 8 (30th June 2021) - Guo, Fuchuan; Han, Mengyuan; Lin, Song; Ye, Hui; Chen, Jiedong; Zhu, Hongni; Lin, Wenting
Abstract : Abstract: Enteromorpha prolifera polysaccharide (EP) has been shown to exhibit hypolipidemic and hypoglycemic activities in various experimental models. Here, an 1 H‐NMR‐based metabolomic study was conducted to explore the regulatory effects of EP on serum metabolic changes in obese hamsters. High‐fat diet (HFD)‐fed hamsters were orally administrated with EP (300, 450, or 600 mg/kg) once daily for 12 weeks. Compared with HFD‐fed hamsters, EP treatment (450 and 600 mg/kg) significantly decreased the body weight (by 8.69 and 8.24%), liver weight (by 7.87 and 8.25%), epididymal white adipose tissue (by 19.54 and 17.26%), perirenal white adipose tissue (by 28.09 and 28.94%), serum total cholesterol (by 24.31 and 18.61%), triglyceride (by 30.64 and 31.38%), and low‐density lipoprotein cholesterol (by 38.26 and 36.30%), respectively. In addition, EP intervention also significantly decreased hepatic cholesterol (by 23.20, 38.16, and 34.57%) and triglyceride content (by 17.78, 41.47, and 35.50%) as well as serum levels of alanine aminotransferase (ALT) and ALT/aspartate aminotransferase (AST) ratio. The serum samples of normal diet (ND) group, HFD group and HFD + EP 450 mg/kg (HFD + MEP) group were further analyzed by 1 H‐NMR spectroscopy. Compared with ND group, 17 and 2 metabolites were significantly upregulated and downregulated in HFD group, respectively. Interestingly, EP treatment significantly downregulated nine metabolites and upregulated one metabolite when compared to those in HFD group. Our results indicated that EP intervention partially ameliorated HFD‐induced metabolic dysfunction, and the most prominent metabolic pathways included citrate cycle, synthesis and degradation of ketone bodies, pyruvate metabolism, valine, leucine and isoleucine degradation, and arginine biosynthesis. Practical Application: Enteromorpha prolifera polysaccharide (EP), the main active component of Enteromorpha prolifera, is reported to have many biological activities. However, the antiobesity effect of EP and its corresponding metabolic mechanism have not been reported so far. The results of this study confirmed the antiobesity effect of EP on HFD‐induced obese hamsters and elucidated its possible metabolic mechanism. Our study highlighted that EP might be used in weight‐loss functional foods.